2014
DOI: 10.17221/62/2013-agricecon
|View full text |Cite
|
Sign up to set email alerts
|

Macroeconomic factors influencing interest rates of microfinance institutions in the Latin America and the Caribbean

Abstract: Agricultural output in developing countries still represents a substantial part of the GDP. Th is ratio has actually increased in some areas such as the Latin America. As such, there is an increasing importance of microfi nance institutions (MFIs) focusing on the activities associated with agriculture and encouraging entrepreneurship in agriculture and in the rural communities in general. Th e contribution of microfi nance institutions consists mainly in providing special-purpose loans, usually without collate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 28 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…Modeling Determinants of Sources of Funds Janda and Zetek (2018) used both the factors (internal & external) to develop an econometric model. For deriving such a model, the same method has been followed here.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Modeling Determinants of Sources of Funds Janda and Zetek (2018) used both the factors (internal & external) to develop an econometric model. For deriving such a model, the same method has been followed here.…”
Section: Methodsmentioning
confidence: 99%
“…The sources of funds for MFI play a vital role on their overall performance. The microfinance industry in Bangladesh optimally utilizes the sources of funds (Mia & Rana, 2018).Costs of funds depend on the sources of funds ,and the fund's sources affect the rate of interest of MFIs (Al-Azzam & Mimouni, 2016;Assefa & Meesters, 2013;Cotler & Almazan, 2013;Dorfleitner & Mosch, 2013;Fernando, 2006;Ghosh, 2013, Heinen & Baquero, 2013Janda & Zetek, 2018;Roberts, 2013). Policymakers and academicians have been considering interest rates as a major issue in microfinance since its inception (Fernando, 2006, Mersland & Khafagy, 2013Rosenberg et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…MFIs in different regions present different characteristics, so they might not be affected in the same way by monetary policy restrictions. Despite the fact that the practice of microfinance emerged around the same time in Asia and Latin America, MFIs evolved differently in both regions (Miller, 2003;Weiss & Montgomery, 2005;Servin et al, 2012;Janda & Zetek, 2014). MFIs in Latin American countries have made significant progress in financing via markets and deposits, which made them less dependent on donations and subsidies.…”
Section: Differences Between Asia and Latin Americamentioning
confidence: 99%
“…This interaction is inverse, because these institutions affect the growth of GDP, loans given for financial support help the overall economic growth (Maksudova, 2010). Janda and Zetek(2014) have found that macroeconomic factors have a significant impact in influencing interest rates of the microfinance institutions. These factors have a significant impact on the overall profitability of the MFIs.…”
Section: Chart 1 Microfinance's Dynamicsmentioning
confidence: 99%